2014
DOI: 10.2463/mrms.2013-0084
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Robust Estimation of Diffusional Kurtosis Imaging (DKI) Parameters by General Closed-form Expressions and their Extensions

Abstract: Diffusional kurtosis imaging (DKI) for clinical imaging involves time-consuming computation and demonstrates low robustness. Standard estimation of DKI parameters is based on an extension of Stejskal-Tanner's signal model with squared b-value term and is a leastsquares fitting problem. The use of numerical methods for computation requires time, and estimation of DKI parameters is noise sensitive and often produces noisy results, such as images with pepper noise.In this study, we propose general closed-form sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…However, the kurtosis and diffusion tensors contain the majority of the information obtainable with small diffusion weightings (Jensen and Helpern, 2010), and so this loss is likely to be minor when low b-value dMRI methods, such as DKI, are employed. In addition, by basing the modeling solely on these two tensors, KANDO can benefit from the advanced post-processing methods already available for DKI (André et al, 2014; Ghosh et al, 2014; Glenn et al, 2014; Kuder et al, 2012; Tabesh et al, 2011; Masutani and Aoki, 2014; Poot et al, 2010; Tax et al, 2014; Veraart et al, 2013; Veraart et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…However, the kurtosis and diffusion tensors contain the majority of the information obtainable with small diffusion weightings (Jensen and Helpern, 2010), and so this loss is likely to be minor when low b-value dMRI methods, such as DKI, are employed. In addition, by basing the modeling solely on these two tensors, KANDO can benefit from the advanced post-processing methods already available for DKI (André et al, 2014; Ghosh et al, 2014; Glenn et al, 2014; Kuder et al, 2012; Tabesh et al, 2011; Masutani and Aoki, 2014; Poot et al, 2010; Tax et al, 2014; Veraart et al, 2013; Veraart et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…HCU, Hiroshima, Japan). 31 Prior to DKI calculation, the amount of noise (η) was estimated from the mean value of signals at air region in the image. 20 The DKI parameters for a single direction can be determined with the following Equation (1) as described in previous studies 20 , 21 : where S is the diffusion-weighted signal intensity at the given b value, S 0 is the signal intensity at b = 0 s/mm 2 , D app is the mean diffusivity (MD), and K app is the apparent kurtosis coefficient (dimensionless).…”
Section: Methodsmentioning
confidence: 99%
“…Here voxels with MK value outside the physiologically reasonable range (0≦MK≦2) were judged as containing calculation error. 31 Though this range of acceptable MK value was set originally presuming normal white matter, recent studies have suggested that MK comes into this range even in severely pathological tissues like glioma and multiple sclerosis. 34 , 35 Using the back-projected FA skeleton as an ROI, the rates of error voxels were compared between the controls and the iNPH patients using Student’s t-test.…”
Section: Methodsmentioning
confidence: 99%
“…The brief calculation procedure for each pixel was as follows. First, quadratic-function curve fitting was performed for the b-value-related signal changes in each encoding direction, separately (a closed-form method was applied) [ 10 , 14 ]. …”
Section: Methodsmentioning
confidence: 99%
“…However, the long acquisition time of DKI resulting from the requirements for multiple b-values and the large number of diffusion encoding directions (NEDs) of the raw diffusion-weighted images (DWIs) remains a problem [ 3 , 10 ]. A typical conventional protocol can consist of 30 uniformly distributed encoding directions in three to six different b-values between 0 and 3,000 s/mm 2 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%